1974
DOI: 10.3758/bf03196925
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and recall by children and adults as a function of variations in memory encoding instructions

Abstract: In four experiments Ss were instructed to learn a set of 40 words by producing implicit associative responses to each item (association instructions), by repeating items over and over (repetition instruction), or by using their own devices (neutral instructions). Experiment I showed that recognition memory (RM) accuracy was greatest under association instructions for adults and children and least under repetition instructions for children. The implications of these results for a frequency theory analysis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1974
1974
1976
1976

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Acoustic distractors elicited a significant number of false-recognition responses at both age levels, and semantic distractors (synonyms and antonyms) appeared to increase in potency with age. In 411 contrast, in a study by Hall and Pierce (1974) rhyme distractors produced no more false recognitions than did control words for either elementary school children or college students, while verbal associates were effective distractors at both age levels. The somewhat older age of the children tested in this study (a mixed group of third and fourth graders) could account for the failure to obtain a developmental interaction.…”
mentioning
confidence: 74%
“…Acoustic distractors elicited a significant number of false-recognition responses at both age levels, and semantic distractors (synonyms and antonyms) appeared to increase in potency with age. In 411 contrast, in a study by Hall and Pierce (1974) rhyme distractors produced no more false recognitions than did control words for either elementary school children or college students, while verbal associates were effective distractors at both age levels. The somewhat older age of the children tested in this study (a mixed group of third and fourth graders) could account for the failure to obtain a developmental interaction.…”
mentioning
confidence: 74%
“…As and Freund (1970). Although Underwood (1969) had Postman has cautioned, "in the analysis of organiza-first proposed that the verbal associative attribute tional processes, and in particular of the conditions of generally was useful only for retrieval, several recent retrieval, it is not safe to assume that the same principles studies (e.g., Hall & Pierce, 1974;Zechmeister & Gude, govern the processing and recall of categorized and 1974) have suggested that verbal associative information of non-categorized lists" (Postman, 1972, p. 17).…”
mentioning
confidence: 99%
“…However, retention of the kind of encoding act ivity indicates that Ss have available other information than frequency by which to make a recognition decision. Light & Selhorst (1971) and Hall & Pierce (1972) have reported that recognition memory for common words was more accurate after Ss received instructions to produce associations to items at the time of study than after Ss were instructed to repeat study items or received neutral instructions. These results are in apparent conflict with predictions derived from the frequency theory of recognition memory ( Freund, 1970).…”
Section: Notementioning
confidence: 99%